Roles of the environment, vegetation and spatial structure in the species composition of the Heteroptera community. Issue 1 (2nd January 2020) - Diez, Fernando; Coscarón, MaríA Del Carmen
Abstract : In the present study, we assessed the assemblages of terrestrial Heteroptera along a 500-km latitudinal and 500-km longitudinal gradient in the north of Argentine Patagonia and investigated the potential effects of the environment, vegetation factors and spatial structure on the community composition of terrestrial Heteroptera at regional scale. To identify the terrestrial Heteroptera assemblages and evaluate their association with different factors, we used multivariate analyses. A total of 840 samplings were carried out in 21 sites of three phytogeographic provinces (Patagonian steppe, Subantarctic province and Monte) along two sampling years. We captured a total of 2007 specimens, 1890 of which were identified to species and morphospecies level, and 57 of which were immature-stage specimens that could not be identified due to their unknown morphology and biology. We identified two distinct terrestrial Heteroptera assemblages: a) one from sites belonging to the Patagonian steppe and Subantarctic province and b) the other from sites belonging to the Patagonian steppe and Monte. The variation in the terrestrial Heteroptera assemblages explained mainly by Isothermality was significant and greater than that explained by the vegetation and the spatial structure. The results showed that, in northern Argentine Patagonia, the different Heteroptera assemblages are more associated with geographic areas with different environmental conditions than with areas with different vegetation types. The results also suggest that the variation in Heteroptera species composition at regional scale is driven by environmental variables related to thermal amplitude and precipitation.